Atomic childhood around 1980. (January 2016) - Freeman, Lindsey A
In On Hashish, Walter Benjamin writes that he would "like to write something that comes from things the way wine comes from grapes." Here I try a similar project by squeezing things from my past that have been fermented over time with memory to show the intoxication of an atomic childhood. I take as the starting point objects and spaces from my experiences in and around the atomic city of Oak Ridge, Tennessee, which may or may not be shared by others who encountered atomic Appalachia. Stretching beyond my own experience, I seek to add to the growing body of thinking about the connections between materiality and memory by adding the atomic as a dynamic example of matter's vibrancy.